Management Of Menstrual Problems In Perimenopausal Women- A Case Report - Anjum, Sadaf; Dhiman, Kamini (International Research Journal of Ayurveda & Yoga, 2021)
Perimenopause is the period during which a woman passes from reproductive to non-reproductive stage and it covers 4-7 years before and after menopause. Periods occur late or early, and the flow becomes heavier or lighter than previous. Acharya Sushruth has divided Madhyamavastha (middle age) into 4stages and the age between 41-70 yrs. comes under Parihani stage (deterioration) where there is deterioration of dhatus (body tissues) occur. In Samhitas various symptoms are described in the context of Yonirogas (gynecological disorder) which can be seen in perimenopausal period. The present case report documents the efficacy of Ayurvedic treatment in improving the perimenopausal symptoms. A case was taken for study with symptoms of shortened menstrual cycle of 15days, prolonged heavy bleeding associated with pain in lower abdomen during menses, backache and loss of appetite. The patient was given Pushyanug churna, Rasayan churna vati, Chandraprabhi vati, Singhnand guggulu after meal two times a day orally and syrup M liv before meal two times a day orally for three months. Ayurveda offers effective modalities and herbal formulations for the management of perimenopausal symptoms without any side effects. The drugs used in this case are having Deepana (appetizer), Pachana (digestive), Anulomana, Shothahara (anti-inflammatory), Raktprasadan (blood purifier), Balya (strengthen) and Rasayana (rejuvenation) properties and results showed there was a marked improvement in symptoms like pain was reduced, and cycle was regularized with moderate bleeding. Therefore, it could be a safe alternative to the modern drugs.